温哥华抗争分校后援会给与经济援助的信 - 曾石泉; Zeng, Shiquan (1921)
A letter from the Chinese community in Vancouver about them sending financial assistance to Victoria in support of their protest against the segregation of Chinese children in Public Schools. 18 December 1921 （[中华民国]十年十二月十八）